Synthesis, characterization and cytotoxic activity of S-benzyldithiocarbazate Schiff bases derived from 5-fluoroisatin, 5-chloroisatin, 5-bromoisatin and their crystal structures - Abdul Manan, Mohd Abdul Fatah; Crouse, Karen Anne; Mohamed Tahir, Mohamed Ibrahim; Rosli, Rozita; How, Fiona Ni Foong; Watkins, David J.; Slawin, Alexandra Martha Zoya (Springer New York LLC, 2011)
Schiff bases were prepared from S-benzyldithiocarbazate with 5-fluro-, 5-chloro- and 5-bromoisatin. All are potential tridentate nitrogen, oxygen, sulfur donors. They were found to be selectively active against MCF-7 cell line (Human non-metastatic mammary gland adenocarcinoma cell line). The bromide and fluoride compounds were the most active with IC50 values of 6.40 lM (2.6 lg/mL) and 9.26 lM (3.2 lg/mL) respectively while the chloride derivative was weakly active with an IC50 value of 38.69 lM (14.0 lg/mL). The cytotoxic activity of the halo substituted isatins against the breast cancer cell lines tested is in the order of Br>F>Cl. Planarity of the isatin ring in the Schiff bases can be arranged in the following order SB5FISA[SB5ClISA[SB5BrISA while the perpendicularity of the benzyl ring towards the dithiocarbazate plane can be ordered as follows, SB5FISA>SB5BrISA>SB5ClISA.